1999
DOI: 10.1080/02626669909492292
|View full text |Cite
|
Sign up to set email alerts
|

Approche quantitative de l'érosion hydrique à différentes échelles spatiales: bassin versant de l'Oued Mina

Abstract: Nous examinons ici le phénomène très complexe de l'érosion hydrique de bassins versants. L'approche adoptée consiste d'une part à quantifier l'érosion à plusieurs échelles spatiales, au sens de la méthode Wischmeier, de la simulation de pluies sur 1 et 87 m , de micro-bassins expérimentaux, de retenues collinaires et d'un barrage en exploitation, et d'autre part à rechercher un modèle régressif pouvant expliquer la relation débit solide-débit liquide pour les différentes formes d'érosion. Une zone de marnes du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Since the Independence of Algeria, the total number of dams in exploitation at national level increased from 14 in 1962 to 65 in 2014 and, if we add the inter-basin water transfer major works, The watershed of Wadi Mina (6048 km 2 , northwest Algeria) is the subject of numerous works in the field of water erosion and siltation of dams [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%
“…Since the Independence of Algeria, the total number of dams in exploitation at national level increased from 14 in 1962 to 65 in 2014 and, if we add the inter-basin water transfer major works, The watershed of Wadi Mina (6048 km 2 , northwest Algeria) is the subject of numerous works in the field of water erosion and siltation of dams [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of this kind of data has led many researchers to develop relationships for the estimation of this factor through annual or monthly rainfall. Many relationships have been established to calculate the R factor according to annual and monthly rainfall (annual rainfall, Fournier index, modified Fournier index) around the world (Roose, 1977;Renard & Freimund, 1994;Touabia, 1999;De Luis et al, 2010;Diodato et al, 2007;Torri et al, 2006); Yang et al, 2003;Loureiro et al, 2001;Ufoegbune et al, 2011;USDA-ARS, 2008). Yu et al(1996) and Renard et al (1994) have shown that in Australia and the United States respectively, the annual rainfall is highly correlated with the R factor.…”
Section: Introductionmentioning
confidence: 99%
“…For each rainfall event, EI 30 is calculated as the product of the kinetic energy of rainfall (E) and the maximum intensity over 30 min. To estimate R, many relationships based on annual or monthly rainfall, and on the Fournier index or modified Fournier index, have been developed (Cohen et al 2005;Coutinho and Tomas 1994;Da Silva 2004;De Luis et al 2010;Diodato 2004;Diodato 2005;Diodato and Bellocchi 2007;Kalman 1970;Loureiro and Coutinho 2001;Meddi 1992;Morgan 1996;Renard and Freimund 1994;Roose 1977;Torri et al 2006;Touabia 1999;Ufoegbune et al 2011;Usda 2008;Yang et al 2003). Yu and Rosewell (1996) and Renard and Freimund (1994) have shown that annual rainfall is strongly correlated with R in Australia and the USA.…”
Section: Introductionmentioning
confidence: 98%
“…For their part, Mati et al (2000) subdivided annual rainfall in order to develop two models according to the agroclimatological setting of the rainfall gauging station. In Mediterranean countries, this approach has been used to develop a representative formulation of rainfall erosivity to be used instead of R of the universal equation: in Southern Portugal (Coutinho and Tomas 1994), in Algeria (Touabia 1999), in Morocco (Kalman 1970), in Spain (De Luis et al 2010, and in Italy (Diodato 2004;Torri et al 2006;Diodato 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation